High-entropy halide material and preparation method and application thereof
Through the preparation of high-entropy halide materials, the atomic ratio and structure are regulated, the problem of insufficient electrochemical performance of halide solid electrolytes is solved, the conductivity and stability of solid-state batteries are significantly improved, and the cycle life is extended.
Patent Information
- Application Number
- CN202311216252.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-03-21
AI Technical Summary
The reduction potential of the halide solid electrolyte is low and is easy to react with lithium metal, resulting in structural damage and battery failure, and its electrochemical performance needs to be further improved to promote the practical application of solid-state batteries.
Using high-entropy halide material, whose chemical formula is LiaMbXc, through the regulation of atom selection and atomic ratio, a high-entropy halide solid electrolyte with a good crystal structure is prepared to improve its conductivity and chemical stability.
It significantly improves the lithium-ion conductivity, stability and cycle life of solid-state batteries, and solves the problem of insufficient electrochemical performance of halide solid-state electrolytes.
Smart Images

Figure CN119660812A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a high entropy halide material and a preparation method and application thereof. Background Art
[0002] As society continues to explore new energy, lithium-ion batteries are widely used in consumer electronics, new energy vehicles and other fields. Traditional lithium-ion batteries have serious safety risks due to the use of liquid electrolytes. Solid electrolytes, due to their inherent high safety, make solid-state batteries expected to become the main force in the next generation of lithium batteries.
[0003] At present, solid electrolytes mainly include polymer electrolytes, sulfide electrolytes, oxide electrolytes and halide electrolytes. Among them, the main advantages of halide solid electrolytes are wide electrochemical window, good room temperature ionic conductivity, and up to 10 -3 S / cm, good mechanical ductility and easy to cold press form.
[0004] However, the reduction potential of halide solid electrolytes is low and they are easy to react with lithium metal, thus causing problems such as structural damage of the solid electrolyte and battery failure. The development of low-cost solid electrolytes with high room temperature ionic conductivity and high electrochemical stability can greatly promote the practical application of solid-state batteries. Summary of the invention
[0005] In view of this, the present invention provides a high entropy halide material and a preparation method and application thereof, the main purpose of which is to solve the technical problem that the electrochemical performance of halide solid electrolytes needs to be improved.
[0006] In one aspect, the present invention provides a high entropy halide material having the chemical formula:
[0007] Li a M b X c Formula I;
[0008] In Formula I, M is selected from at least five metal elements of Groups IIA, IIB, VB, VIB, VIIB and VIIIB; X is selected from at least one of the halogen elements;
[0009] Wherein, a, b and c are the molar ratios between the corresponding elements;
[0010] 1≤a≤6, 0.1≤b≤2, 4≤c≤8;
[0011] Subscripts a, b, and c are all rational numbers;
[0012] The high entropy halide material is neutrally charged.
[0013] Optionally, in Formula I, M is selected from at least 5 metal elements of Mg, V, Cr, Mn, Fe, Co, Ni, Cu, Zn and Cd.
[0014] Optionally, in Formula I, X is selected from at least one of F, Cl, Br and I;
[0015] Optionally, the chemical formula of the high entropy halide material comprises:
[0016] Li2Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Cl4,
[0017] Li 1.6 Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 Cl4,
[0018] VxV 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 Cl8,
[0019] Li2Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Br4 or
[0020] Li 1.6 Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 Br4.
[0021] The present invention prepares a synthetic high-entropy halide solid electrolyte compound by selecting atoms in a solid electrolyte and regulating the atomic ratio. When the selection of atoms and the atomic ratio in the solid electrolyte conform to the general chemical formula of the solid electrolyte, it provides an atomic basis for the solid electrolyte to have a better crystal structure, and is also beneficial to significantly improve the electrical conductivity and chemical stability of the solid electrolyte.
[0022] The high entropy halide provided by the present invention has a specific chemical composition arranged and / or bonded by crystallization and non-bonding, and as a solid electrolyte material, it has good lithium ion conductivity, good stability and long cycle life.
[0023] In a second aspect, the present invention provides a method for preparing the above-mentioned high entropy halide material, the preparation method comprising the following steps:
[0024] S1: mixing raw materials containing lithium halide and metal halide according to a ratio and pulverizing them to obtain mixed powder;
[0025] S2: The mixed powder in step S1 is subjected to heat treatment in an inert atmosphere under closed conditions to obtain the high entropy halide material.
[0026] The specific annealing method adopted by the present invention affects most of the chemical composition, surface chemical composition, chemical structure (such as bond type and arrangement), crystallinity, stability and conductivity of these high entropy halide solid electrolyte compounds and other properties of these high entropy halide solid electrolyte compounds. The high entropy halide solid electrolyte compound of the present invention is semi-amorphous.
[0027] Optionally, in step S1, the lithium halide includes lithium chloride and lithium bromide.
[0028] Optionally, in step S1, the metal halide is selected from at least five of metal magnesium halide, metal vanadium halide, metal chromium halide, metal manganese halide, metal iron halide, metal cobalt halide, metal nickel halide, metal copper halide, metal zinc halide and metal cadmium halide.
[0029] Optionally, in step S1, the metal halide is a mixture of magnesium chloride, vanadium dichloride, chromium dichloride, manganese dichloride, ferric dichloride and cobalt dichloride.
[0030] Optionally, in step S1, the metal halide is a mixture of magnesium bromide, vanadium dibromide, chromium dibromide, manganese dibromide and iron dibromide.
[0031] Optionally, in step S1, the molar ratio of the lithium halide to the metal halide is 1 to 6:1.
[0032] Optionally, the molar ratio of the lithium halide to the metal halide is selected from any value of 1, 2, 3, 4, 5, 6 or any range between two values.
[0033] Optionally, in step S1, the molar amounts of the components in the metal halide are equal.
[0034] Optionally, in step S3, the temperature of the heat treatment is 100 to 800° C., and the time of the heat treatment is 1 to 480 hours; and the inert atmosphere includes an argon atmosphere.
[0035] Optionally, the temperature of the heat treatment is selected from any value among 100℃, 150℃, 200℃, 250℃, 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, 650℃, 700℃, 750℃, 800℃ or any range between two of them.
[0036] Optionally, in step S1, the raw materials are mixed by ball milling, the ball-to-material ratio is 5 to 40:1, the rotation speed of the ball milling is 100 to 500 r / min, and the time of the ball milling is 1 to 40 h.
[0037] Optionally, the ball-to-material ratio is any value selected from 5, 10, 15, 20, 25, 30, 35, 40, or a range between any two of them; the rotation speed is any value selected from 100, 200, 300, 400, 500 r / min, or a range between any two of them; the ball milling time is any value selected from 1, 5, 10, 15, 20, 25, 30, 35, 40 h, or a range between any two of them.
[0038] The present invention adopts ball milling mixing to improve the uniformity of mixing between raw materials, which is conducive to making the synthesis in the subsequent synthesis process easier and increasing the synthesis rate, and is conducive to improving the crystallinity of the prepared solid electrolyte.
[0039] Optionally, the mixed powder is pressed into a sheet to obtain a sheet, and the sheet is heat-treated in an inert atmosphere under closed conditions.
[0040] The invention first makes the mixed powder into sheets and then performs heat treatment, which has a better effect.
[0041] The present invention provides a specific method for preparing a high entropy halide material, comprising the following steps:
[0042] The raw materials include lithium halide and metal halide;
[0043] The metal halide includes metal halides corresponding to at least five metal elements among Mg, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, and Cd.
[0044] According to the general stoichiometric ratio, lithium halide precursor and halides corresponding to at least five metal elements are weighed and mixed and ball-milled to obtain a mixed powder; the mixed powder is pressed into tablets, then heat-treated and sintered in an argon atmosphere, and then ground to obtain the target product.
[0045] The chemical formula of the compound is Li a M b X c ;
[0046] M includes at least 5 metal elements from Groups IIA, IIB, VB, VIB, VIIB, and VIIIB, and X includes one or more halogen elements; wherein 1≤a≤6, 0.1≤b≤2, and 4≤c≤8; wherein subscripts a, b, and c are all rational numbers; wherein the compound is neutrally charged.
[0047] In a third aspect, the present invention provides a halide solid electrolyte, wherein the material of the halide solid electrolyte includes the above-mentioned high entropy halide material.
[0048] In a fourth aspect, the present invention provides a solid-state battery, comprising a solid-state electrolyte, wherein the solid-state electrolyte comprises the above-mentioned halide solid-state electrolyte.
[0049] In a fifth aspect, the present invention provides the use of the above-mentioned high entropy halide material or the above-mentioned halide solid electrolyte in a semi-solid lithium ion battery, a quasi-solid lithium ion battery or an all-solid lithium ion battery.
[0050] The solid electrolyte provided by the present invention is applied to all-solid-state batteries, which can greatly improve the cycle life of the all-solid-state batteries.
[0051] Compared with the prior art, the present invention has the following beneficial effects:
[0052] The high-entropy halide solid electrolyte lithium metal prepared by the present invention has good lithium ion conductivity, good stability and electrochemical stability, and can greatly improve the cycle life of the solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 is Li in Example 1 of the present invention 1.6 Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 XRD powder diffraction test pattern of Cl4 solid electrolyte;
[0054] Figure 2 is Li in Example 1 of the present invention 1.6 Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 Scanning electron microscopy image of Cl4 solid electrolyte;
[0055] Figure 3 is Li in Example 1 of the present invention 1.6 Mg 0.2 V 0.2 Cr 0.2Mn 0.2 Fe 0.2 Co 0.2 Electrochemical impedance spectroscopy of Cl4 solid electrolyte;
[0056] Figure 4 is Li in Example 1 of the present invention 1.6 Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 Electrochemical cycle diagram of an all-solid-state battery assembled with Cl4 solid electrolyte and lithium cobalt oxide positive electrode. DETAILED DESCRIPTION
[0057] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.
[0058] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.
[0059] Example 1 (High Entropy Halide Solid Electrolyte)
[0060] Lithium chloride (LiCl), magnesium dichloride (MgCl2), vanadium dichloride (VCl2), chromium dichloride (CrCl2), manganese dichloride (MnCl2), ferrous chloride (FeCl2), and cobalt dichloride (CoCl2) (powdered) were added into a 100 mL ball mill filled with 8 mm zirconium oxide ball milling beads at a molar ratio of 8:1:1:1:1:1:1 and mixed (the powder was loaded into the ball mill in an argon-filled glove box), and the mass ratio of ball milling medium: mixture powder was 40:1; the mixture was ball milled at 500 rpm / min in a planetary ball mill for 40 hours.
[0061] The ball-milled powder was pressed into a 10 mm diameter disc under a pressure of 2t, then placed in a quartz tube and sealed, and annealed at 650 °C for 20 hours in an argon atmosphere to obtain a solid electrolyte. The chemical formula of the product was detected to be Li 1.6 Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 Cl4.
[0062] Example 2 (High Entropy Halide Solid Electrolyte)
[0063] Lithium bromide (LiBr), magnesium bromide (MgBr2), vanadium dibromide (VBr2), chromium dibromide (CrBr2), manganese dibromide (MnBr2), ferrous bromide (FeBr2) (powder) were added to a 100 ml ball mill containing 8 mm zirconium oxide ball milling beads at a molar ratio of 10:1:1:1:1:1 (the powder was loaded into the ball mill in an argon-filled glove box), and the mass ratio of ball milling media to mixture powder was 40:1. The mixture was ball milled at 500 rpm / min for 40 hours in a planetary ball mill.
[0064] The ball-milled powder was pressed into a 10 mm diameter disc under a pressure of 2t, then placed in a quartz tube and sealed, and annealed at 500 °C for 20 hours in an argon atmosphere to obtain a solid electrolyte. The chemical formula of the product was detected to be Li2Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Br4.
[0065] Example 3 (All-solid-state lithium-ion battery)
[0066] LiCoO2 and Li 1.6 Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 Cl4 (prepared in Example 1) was ground uniformly at a mass ratio of 7:3 to obtain a positive electrode; 100 mg Li 1.6 Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 Cl4 (prepared in Example 1) powder was loaded into a solid-state battery mold with a diameter of 10 mm, and a tablet was pressed at 3 t pressure (solid electrolyte). 10 mg of the above positive electrode was laid flat on one side, and a tablet was pressed at 3 t pressure. Li metal was placed on the other side of the solid electrolyte, and finally the screws of the solid-state battery mold were tightened; Li 1.6 Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 Cl4 solid electrolyte is assembled into Li2CoO2||Li 1.6 Mg 0.2 V0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 Solid-state battery with Cl4||Li configuration.
[0067] The Li prepared in Example 1 1.6 Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 The Cl4 solid electrolyte was characterized by XRD. The characterization results are as follows Figure 1 shown.
[0068] The Li prepared in Example 1 1.6 Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 The Cl4 solid electrolyte was characterized by scanning electron microscopy. The characterization results are as follows Figure 2 shown.
[0069] The Li prepared in Example 1 1.6 Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 The Cl4 solid electrolyte was tested for electrochemical impedance spectroscopy. The test results are as follows Figure 3 As shown, it is explained that the solid electrolyte prepared by the present invention has a higher room temperature ionic conductivity.
[0070] The charge and discharge performance of the solid-state battery prepared in Example 3 was tested, and the charge and discharge performance results are as follows: Figure 4 shown by Figure 4 This shows that the prepared solid-state battery has good cycle stability.
[0071] Li2Mg prepared in Example 2 of the present invention 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 The electrochemical performance of Br4 is similar to that of Example 1.
[0072] In summary, the solid electrolyte prepared by the present invention can have both high electrical conductivity and chemical stability, and has good application prospects in all-solid-state batteries.
[0073] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A high entropy halide material, characterized in that: The chemical formula of the high entropy halide material is: Li a M b X c Formula I; In Formula I, M is selected from at least five metal elements of Groups IIA, IIB, VB, VIB, VIIB and VIIIB; X is selected from at least one of the halogen elements; Wherein, a, b and c are the molar ratios between the corresponding elements; 1≤a≤6, 0.1≤b≤2, 4≤c≤8.
2. A high entropy halide material according to claim 1, characterized in that: In Formula I, M is at least five metal elements selected from the group consisting of Mg, V, Cr, Mn, Fe, Co, Ni, Cu, Zn and Cd.
3. A high entropy halide material according to claim 1, characterized in that: In Formula I, X is selected from at least one of F, Cl, Br and I; and the high entropy halide material is neutrally charged.
4. A high entropy halide material according to claim 1, characterized in that: The chemical formula of the high entropy halide material includes: Li2Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Cl4、 Li 1.6 Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 Cl4、 Li6V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 Cl8、 Li2Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Br4 or Li 1.6 Mg 0.2 V 0.2 Cr 0.2 Mn 0.2 Fe 0.2 Co 0.2 Br4。 5. A method for preparing a high entropy halide material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1: mixing raw materials containing lithium halide and metal halide according to a ratio and pulverizing them to obtain mixed powder; S2: The mixed powder in step S1 is heat-treated in an inert atmosphere under closed conditions to obtain the high entropy halide material.
6. The method for preparing a high entropy halide material according to claim 5, characterized in that: In step S1, the metal halide is selected from at least five of metal magnesium halide, metal vanadium halide, metal chromium halide, metal manganese halide, metal iron halide, metal cobalt halide, metal nickel halide, metal copper halide, metal zinc halide and metal cadmium halide.
7. The method for preparing a high entropy halide material according to claim 5, characterized in that: In step S1, the molar ratio of the lithium halide to the metal halide is 1 to 6:1; Preferably, in step S1, the molar amounts of the components in the metal halide are equal; Preferably, in step S3, the temperature of the heat treatment is 100 to 800° C., and the time of the heat treatment is 1 to 480 hours; the inert atmosphere includes an argon atmosphere; Preferably, in step S1, the raw materials are mixed by ball milling, the ball-to-material ratio is 5 to 40:1, the rotation speed of the ball milling is 100 to 500 r / min, and the ball milling time is 1 to 40 h; The mixed powder is pressed into tablets to obtain sheets, and the sheets are heat treated in an inert atmosphere under closed conditions.
8. A halide solid electrolyte, characterized in that: The material of the halide solid electrolyte includes the high entropy halide material according to any one of claims 1 to 4.
9. A solid-state battery comprising a solid electrolyte, characterized in that: The solid electrolyte comprises a halide solid electrolyte as claimed in claim 11.
10. Use of the high entropy halide material according to any one of claims 1 to 4 in a semi-solid lithium ion battery, a quasi-solid lithium ion battery or an all-solid lithium ion battery.